Influence of weathering and temperature on the electrochemical and microscopical characteristics of CeO2 and CeO2:V2O5 sol-gel thin films. (October 2021) - Balboni, Raphael D.C.; Cholant, Camila M.; Krüger, Luana U.; Moura, Elton A.; Maron, Guilherme K.; Flores, Wladimir H.; Gündel, André; Gatto, Darci A.; Pawlicka, Agnieszka; Avellaneda, Cesar A.O.; Andreazza, Robson
Highlights: CeO2 and CeO2 :V2 O5 with 15 mol% thin films were synthesized and characterized. The films underwent a weathering process in an accelerated weathering test chamber. Films properties were evaluated before and after 900 days of simulated weathering. Electrochemical properties were also evaluated at different temperatures. The properties remained promising after 2.5 years of exposure to the weathering. Abstract: Thin films of cerium dioxide (CeO2 ) and cerium dioxide doped with vanadium pentoxide (CeO2 :V2 O5 ) were prepared through sol-gel route and spin coating deposition, for use as smart materials. This work evaluated films that underwent a weathering process in an accelerated weathering test chamber and the changes in their properties. The influence of the temperature was also studied electrochemically. Regarding the weathering process, there were variations in the charge insertion capacity during the investigated period. However, at the end of the 900 simulated days, the CeO2 :V2 O5 presented interesting values. For the EIS analyses, the curve (Nyquist plot) remained about 45° inclination, suggesting a diffusional process. The morphological and structural analyses demonstrated that by doping the film, occurs a reduction on the degradation, although the structure showed no changes. For different temperatures, the film becomes more resistive as the temperature increases. The chronocoulometry showed that the charge insertion capacity increases with temperature. Graphical abstract: Image, graphical abstract